Le droit de vote accordé aux femmes britanniques à l’issue de la Première Guerre mondiale : une récompense pour les services rendus ? - Véronique Molinari (Revue LISA)
The fact that 8.5 million British women obtained the right to vote at the end of the First World War has often been attributed to women’s war work and presented as a kind of reward for services rendered to the nation. Such an opinion, however, is difficult to maintain. While some people may have changed their view of the value of women when confronted with their participation in the war effort, prejudice certainly did not disappear as quickly as both the press and politicians would have liked people to believe – mainly for propaganda purposes. Besides, many elements contradict the idea of the vote as a reward: the mass dismissal of women workers at the end of the war and the volte-face of the press in the following years, the age restriction imposed by the Representation of the People Act that left most women war-workers out of the electorate because they were under 30, or again the reluctance of the government to include women in an electoral reform made necessary to allow soldiers to vote. For one should not forget that the electoral reform of 1918 was never meant for women and that women’s suffrage was, in fact, the only measure in the whole bill not to be approved unanimously.